Nuclear Policy and the Changing Dynamics of Decision-Making - Keith Gottschalk (The Thinker)
Under the apartheid regime nuclear policy was decided by the president, with most of the cabinet being in the loop. The African National Congress (ANC) in exile sought to discover the facts, and to campaign against the apartheid regime acquiring nuclear weapon capabilities. Between 1991 and 1994, the ANC’s Science and Technology Policy group played a role in lobbying on nuclear policy issues, alongside some NGOs, culminating in the February 1994 conference on nuclear policy. After the came to power in April 1994, inaugurating democracy, the nuclear lobby within the bureaucracy and parastatals influenced the relevant ANC directors-general, cabinet ministers and one president. Statutory and regulatory agencies were compromised. Civil society organisations alone took the lead in opposing nuclear energy, and were partly successful.